Acupuncture for nasal congestion in COVID-19: A protocol for systematic review and meta-analysis. Issue 2 (14th January 2022) - Dong, Zhibin; Guo, Jinyun; Deng, Tingting; Zhang, Jingwen; Lv, Xinwei; Zhang, Kaixin; Ma, Yuxia; Ma, Yuning
Abstract: Background: From the end of 2019 to now, coronavirus disease 2019 (COVID-19) has put enormous strain on the world's health systems, causing significant deaths and economic losses worldwide. Nasal congestion, one of the symptoms of COVID-19, poses considerable problems for patients. In China, acupuncture has been widely used to treat nasal congestion caused by COVID-19, but there is still a lack of evidence-based medical evaluation. Methods: According to the retrieval strategies, randomized controlled trials on the acupuncture for COVID-19 nasal congestion were obtained from China National Knowledge Infrastructure, WanFang, VIP, PubMed, Embase, and Cochrane Library, regardless of publication date, or language. Studies were screened based on inclusion and exclusion criteria, and the Cochrane risk bias assessment tool was used to evaluate the quality of the studies. The meta-analysis was performed using Review Manager (RevMan 5.3) and STATA 14.2 software. Ultimately, the evidentiary grade for the results will be evaluated. Results: The study will provide a high-quality and convincing assessment of the efficacy and safety of acupuncture in the treatment of COVID-19's nasal congestion and will be published in peer-reviewed journals. Conclusion: Our findings will provide references for future clinical decision and guidance development. PROSPERO registration number: NO.CRD42021299482. Abstract : Supplemental Digital Content is available in the text